LncRNA-AK012226 Is Involved in Fat Accumulation in db/db Mice Fatty Liver and Non-alcoholic Fatty Liver Disease Cell Model - Chen, Xingtian; Xu, Yangzhi; Zhao, Dan; Chen, Ting; Gu, Chengxin; Yu, Ganxiang; Chen, Ken; Zhong, Yun; He, Jie; Liu, Shiming; Nie, Yuqiang; Yang, Hui (Frontiers in Pharmacology, 2018)
Instances of obesity and related metabolic abnormalities are increasing across the world. Nonalcoholic fatty liver disease (NAFLD) is a common disorder in obese people and is becoming the leading cause of hepatocellular carcinoma (HCC). Recently, lncRNAs have been proven to play remarkable roles in numerous biological processes and human diseases, including NAFLD. However, the function of lncRNA in NAFLD pathogenesis remains largely unknown. The aim of this study was to explore the lncRNA expression profile in NAFLD mice and to identify novel lncRNAs involved in the pathogenesis of NAFLD. We performed microarray analysis to compare the expression profiles of lncRNAs and mRNAs in the liver of diabetic db/db mice with NAFLD and normal mice. A total of 3360 lncRNAs (2048 up-regulated and 1312 down-regulated) and 2685 mRNAs (1195 up-regulated and 1490 down-regulated) were found to be differentially expressed between the NAFLD and control groups. Real-time PCR validation of five differentially expressed lncRNAs in the liver samples was consistent with the microarray results. Besides, the up-regulated lncRNA, AK012226, was also significantly increased in an NCTC1469 NAFLD cellular model. Thus, the up-regulated lncRNA, AK012226, was chosen for subsequent studies. A co-expression network of AK012226–mRNAs was constructed and bioinformatic analysis of these co-expressed mRNAs indicated that they were enriched in the PPAR signaling pathway. Furthermore, Nile red staining and flow cytometry analysis revealed that knockdown of AK012226 by siRNA significantly reduced the lipid accumulation in the NCTC1469 cells treated with free fatty acids. In conclusion, the present study identifies the dysregulated lncRNAs and mRNAs involved in NAFLD, and in particular, a novel lncRNA, AK012226, was identified to be associated with lipid accumulation in NAFLD.